2022
DOI: 10.1021/acs.jpclett.2c01636
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing Confinement Regime in Terahertz HgTe Nanocrystals Studied under Extreme Conditions of Temperature and Pressure

Abstract: While HgTe nanocrystals (NCs) in the mid-infrared region have reached a high level of maturity, their far-infrared counterparts remain far less studied, raising the need for an in-depth investigation of the material before efficient device integration can be considered. Here, we explore the effect of temperature and pressure on the structural, spectroscopic, and transport properties of HgTe NCs displaying an intraband absorption at 10 THz. The temperature leads to a very weak modulation of the spectrum as oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…30 Furthermore, the transport is strongly dependent on the temperature, making the sample cooling a viable strategy to reduce the dark current as opposed to a pristine array of degenerately doped NCs. 12,18,19,24,31 The extracted activation energy is 163 meV (Figure S9), which corresponds to half of the intraband gap energy. This is the highest value reported for transport in intraband particles at this wavelength, highlighting the benefit of our geometry.…”
Section: Resultsmentioning
confidence: 99%
“…30 Furthermore, the transport is strongly dependent on the temperature, making the sample cooling a viable strategy to reduce the dark current as opposed to a pristine array of degenerately doped NCs. 12,18,19,24,31 The extracted activation energy is 163 meV (Figure S9), which corresponds to half of the intraband gap energy. This is the highest value reported for transport in intraband particles at this wavelength, highlighting the benefit of our geometry.…”
Section: Resultsmentioning
confidence: 99%
“…1.5–2.5 GPa from zinc blende (ZB) to cinnabar, a significantly higher phase transition pressure at ca. 2.9 GPa has been theoretically predicted for 15 nm HgTe NPs . Lee et al.…”
Section: Pressure-induced Inorganic Np Atomic Structure Phase Transitionmentioning
confidence: 90%
“…2.9 GPa has been theoretically predicted for 15 nm HgTe NPs. 79 Lee et al reported that the spinel zero-dimensional (0D) Zn 2 SnO 4 NPs are stable up to 40 GPa. However, one-dimensional (1D) Zn 2 SnO 4 nanostructures irreversibly transition into a new structure that is similar to the orthorhombic structure of CaFe 2 O 4 .…”
Section: Semiconductor Npsmentioning
confidence: 99%
“…In this context, Ag 2 Se is a promising alternative IR semiconductor, having a narrow bulk bandgap of ∼0.05–0.18 eV . As nanoparticles, Ag 2 Se demonstrates extensive photoresponse tunability from the NIR to the long-wave infrared (LWIR) region of the electromagnetic spectrum by varying particle diameter in the range of 2.6–27 nm. The NIR response emerges from the interband energy transition (“the band gap”, between the 1S h and 1S e states), while the MWIR and LWIR response is perceived to be the result of an intraband energy transition from the 1S e to 1P e state. Intraband transitions in IR CQDs have been explored more extensively in the Hg chalcogenide literature, suggesting that energy level filling and stable n-type doping is a result of band edge positions relative to the environmental Fermi level, E F,env . …”
Section: Introductionmentioning
confidence: 99%